Roles and Responsibilities of Parents towards Children's Education in Islamic Perspective - Intan Indah Maharany; Devid Saputra; Evi Febriani; Muhamad Kumaidi (Pusdikra-Publishing.com, 2024)
The family is the first educational institution that helps foster creativity in children. The purpose of writing this article is to describe the roles and responsibilities of parents towards children's education in an Islamic perspective. The research method used is library research. In Islam, the future of children is determined in the family education system. The role of parents is very important in giving birth to children who become a generation of rabbani who have faith, piety and good deeds for their survival in this world and in the hereafter. The Qur'an mentions the qualities that must be possessed by parents as educators, the first and foremost of which is divinity and knowledge of God who will later have wisdom (benefit) or understanding of the truth found through reason and knowledge so as to express gratitude to God, love to give advice to their children about God, do not associate partners with God, order their children to pray, and teach them to be patient when facing difficulties.